The effect of interpersonal, problem solving and technical training skills on performance of Ethiopia textile industry: Continuance, normative and affective commitment as mediators - Metasebia Adula; Zerihun A. Birbirsa; Shashi Kant (Cogent Business & Management, 2023)
This cross-sectional study finds the relationship between interpersonal, problem-solving, and technical training skills and the performance of Ethiopia's textile and clothing industries when mediated by their employee's commitment and continuance. Through a survey conducted in 2023, 426 employees and HR managers of the textile and clothing industry provided cross-sectional data for the study. Co-variation matrix shows the outcome of hypothesis testing. To analyze the findings, structural equation modeling (SEM) was utilized. It was determined whether the data were adequate using exploratory factor analysis (EFA), and the discriminatory validity was assessed using confirmatory factor analysis (CFA). With the aid of the SEM model and AMOS software, mediation analysis was carried out. Because normative commitment's factor loading was under .40, it was amputated or deleted. Its purpose normative commitment as an observed item was unable to account for commitment as a latent variable. As a result, the empirical evidence in the research demonstrated that problem solving and technical expertise are important for the operation of the clothing industry. The results also demonstrate that continuance, normative and affective commitment of employees act as mediators for Interpersonal, problem-solving, and technical training based imparted skills. The research will pave way forward to the textile industries in this regard by highlighting the significance of problem-solving and technical expertise on the performance of the cloth industries in Ethiopia by taking resource-based view and social exchange theory as theoretical lens.
Keywords: 650; affective commitment; continuance commitment; interpersonal skill; problem solving skill; technical Skill